PENGARUH MODEL EXAMPLE NON EXAMPLE BERBANTUAN MEDIA VIDEO TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA - Rahma, Auliyani; Rury Rizhardi; Hermansyah (Journal of Practice Learning and Educational Development, 2025)
This research aimed to determine the influence of the example non-example model assisted by video media on Pancasila Education learning outcomes at SD Negeri 1 Pampangan. This study was prompted by the fact that Pancasila Education learning outcomes at SD Negeri 1 Pampangan were still below the Minimum Completeness Criteria (KKM). The research employed a quantitative approach with a True Experimental Design, specifically using a Posttest-Only Control Design. The population for this study consisted of fourth-grade students at SD Negeri 1 Pampangan. The sample included 16 students from class IV.A and 16 students from class IV.B. Data collection was carried out using a 30-item multiple-choice test. Instrument testing techniques included validity, reliability, difficulty level, and discriminating power. Data analysis involved a normality test, which yielded a significance value of 0.079 (>0.05). A homogeneity test resulted in a significance value of 0.914 (>0.05). An independent samples t-test yielded a significance (2-tailed) value of 0.008 (<0.025). Therefore, it can be concluded that the alternative hypothesis (Ha) is accepted, meaning there is a significant influence of the example non-example model assisted by video media on the learning outcomes of Pancasila Education students at SD Negeri 1 Pampangan.